PEMOGRAMAN ARDUINO MENGGUNAAN PRESSURE TRANSDUCER DAN SENSOR FLOW METER UNTUK PENGUJIAN POMPA HIDRAM - Monalisa Applunia Malelak; Alexius Leonardo Johanis (P3M- Politeknik Negeri Kupang, 2020)
Technological developments require changes and adjustments in various sectors, one of which is digitalization. The hydram pump is an appropriate technology for saving energy, it is simple in manufacture and installation, suitable for the development on areas with limited sources of electrical energy or fuel. Hydram pumps are still being reserchead and developed to obtain optimal models and installations. A faster and more accurate testing of hydram pumps is needed to support the research and development. Arduino is an open source microcontroller platform with a modular system that is easy to assemble and operate together with the embedding of certain sensors. In this study, Arduino programming was carried out to read and display the readings of two pressure sensor transducer and two flow meter sensors for testing on an inch diameter of hydram pump installation model, the sensor readings were way much faster then the test method using a pressure gauge and measuring cup. The percentage of the reading error on the discharge sensor is 5%